2015
DOI: 10.15740/has/ajbs/10.2/148-152
|View full text |Cite
|
Sign up to set email alerts
|

Selection indices for yield improvement in bread wheat under late sown condition

Abstract: Investigation was carried-out to assess the selection indices in 40 genotypes of wheat (Triticum aestivum L.) in limited irrigation under late sowing condition. Sixty-three selection indices, involving grain yield per plant and five yield components, were constructed using the discriminant function technique. The efficiency of selection increased with the inclusion of more number of characters in the index. The selection index based on six characters viz., grain yield per plant, days to maturity, number of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In this context, the selection index consisting of grain yield per plant, the number of grains per main spike, grain weight per main spike and biological yield per plant (X 1 +X 2 +X 3 +X 4 ) could be advantageously exploited in the wheat breeding programs. High efficiency in a selection based on grain yield per plant, the number of grains per main spike, grain weight per main spike and biological yield per plant or in the combination of all these four characters has been reported by Raiyani et al, (2015). The present study revealed that the discriminant function method of making selections in plants appeared to be the most useful as compared to the straight selection for grain yield alone and hence, due weightage should be given to the important selection indices while making the selection for yield advancement in wheat.…”
Section: Selection Indices For Yieldmentioning
confidence: 99%
“…In this context, the selection index consisting of grain yield per plant, the number of grains per main spike, grain weight per main spike and biological yield per plant (X 1 +X 2 +X 3 +X 4 ) could be advantageously exploited in the wheat breeding programs. High efficiency in a selection based on grain yield per plant, the number of grains per main spike, grain weight per main spike and biological yield per plant or in the combination of all these four characters has been reported by Raiyani et al, (2015). The present study revealed that the discriminant function method of making selections in plants appeared to be the most useful as compared to the straight selection for grain yield alone and hence, due weightage should be given to the important selection indices while making the selection for yield advancement in wheat.…”
Section: Selection Indices For Yieldmentioning
confidence: 99%
“…Robinson et al (1951) provided methods for estimating genetic and phenotypic variances and covariance's required to establish selection indices. Numerous studies have been carried out by researchers in this field, dealing with the selection indices in wheat and some other self-fertilized crops, among them were, Wells and Kofoid (1986), Ahmad and Hamdo (2000), Al-Jubouri et al (2006), Taha (2007), Laghari et al (2010), Ahmed et al (2011), Dawod et al (2012), Raiyani et al (2015), Sahar et al (2016) and Ghaed-Rahimi et al (2017), whose results indicated that some election indices, consisting of several traits, outweighed the direct selection of the yield alone, some were characterized by a high relative efficiency and expected genetic improvement as a result of selection.…”
Section: Introductionmentioning
confidence: 99%